A Review on the Proposed Quasi-Concave Quadratic Programming Problems with Bounded Variable: by Counter-example, by Computer Algebra - Das, HK (Dhaka University Journal of Science, 2017)
Abstract not available Dhaka Univ. J. Sci. 65(2): 167-168, 2017 (July)